A de novo transcriptomic analysis to reveal functional genes in Apolygus lucorum. (2nd February 2015) - Cao, De‐Pan; Liu, Yang; Wei, Jin‐Jin; Li, Jian‐Hong; Wang, Gui‐Rong
Abstract: The widespread planting of genetically engineered cotton producing the Cry1Ac toxin has led to significantly reduced pesticide applications since 1997. However, consequently, the number of green mirid bugs (GMB), Apolygus lucorum (Meyer‐Dür) has increased. So far the GMB, instead of the cotton bollworm Helicoverpa armigera (Hübner), has become the major pest in the transgenic Bt cotton field and has influenced cotton yield. Disproportionately, only a few studies on GMB at molecular level have been reported. Libraries from both third instar nymphs and adults were sequenced using Illumina technology, producing more than 106 million short reads and assembled into 63 029 unigenes of mean length 597 nt and N50 813 nt, ranging from 300 nt to 9771 nt. BLASTx analysis against Nr, Swissprot, GO and COG was performed to annotate these unigenes. As a result, 26 478 unigenes (42.01%) matched to known proteins and 107 immune‐related, 320 digestive‐related and 53 metamorphosis‐related genes were detected in these annotated unigenes. Additionally, we profiled gene expression using mapping based differentially expressed genes (DEGs) strategy between the two developmental stages: nymph and adult. The results demonstrated that thousands of genes were significantly differentially expressed at different developmental stages. The transcriptome and gene expression data provided comprehensive and global gene resources of GMB. This transcriptome would improve our understanding of the molecular mechanisms of various underlying biological characteristics, including development, digestion and immunity in GMB. Therefore, these findings could help elucidate the intrinsic factors of the GMB resurgence, offering novel pest management targets for future transgenic cotton breeding.